Sentiments in SVARs - Patrick Fève; Alain Guay (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
This paper investigates the contribution of sentiments shocks to US fluctuations in a Structural VAR setup with restrictions at various frequencies. Sentiments shocks are identified as shocks orthogonal to fundamentals that account for most of the variance of confidence. We obtain that, contrary to news shocks on total factor productivity, sentiments shocks explain little of quantities and prices. Sentiments shocks mostly appear as an idiosyncratic component of confidence. These results are robust to various perturbations.
Keywords: 330